The use of Kuraderm drug in the treatment of basal cell carcinoma of the head and neck - V. Z. Dobrokhotova; A. F. Batsev; T. S. Belysheva (Опухоли головы и шеи, 2016)
Basal cell carcinoma is one of the most common malignancies. Despite a wide range of treatment options and relatively good prognosis of the disease, there may be restrictions on the use of standard methods of treatment because of elderly patients, their physical condition and characteristics of the tumor localization. We provide clinical examples of successful treatment of basal cell carcinoma of the head and neck with Kuraderm BEC5. This is a drug with anti-tumor activity for topical use made on the basis of glycoalkaloids of plants of nightshade family.